Evaluation of Agronomic Traits of Rice in Rice-Fish System Using Correlation and PCA - Kasmiati, Kasmiati; Nasrul, Muhammad (ITScience (Information Technology and Science), 2025)
The rice-fish farming system is an integrated agricultural model that combines rice and fish cultivation in a single field, wherein fish feed has the potential to serve as an additional nitrogen (N) source for rice crops. This study aims to evaluate the effects of nitrogen content in fish feed on the agronomic characteristics of rice and to identify interrelationships between parameters using correlation analysis and Principal Component Analysis . The research was conducted in Laiya Village, Maros Regency, using the Inpari 32 rice variety and four fish feed treatments with varying nitrogen content: 0% (N0), 5% (N1), 7% (N2), and 9% (N3). Results showed that the differences between treatments were not statistically significant regarding the quantitative morphological characteristics of rice, although treatment N2 showed a tendency for the highest yield. Correlation analysis revealed strong positive relationships among the number of productive tillers, plant dry weight, and grain weight per plot. Meanwhile, Principal Component Analysis identified two principal components that explained most of the agronomic variation, with Plant Dry Weight, PT, Grain Weight per Plot, 1000-Grain Weight, and Panicle Length as dominant contributors. These results indicate that nitrogen management through fish feed has the potential to sustainably improve nutrient efficiency and rice productivity in rice-fish farming systems.